2021
DOI: 10.3389/fpsyg.2020.613244
|View full text |Cite
|
Sign up to set email alerts
|

Compulsive Internet Pornography Use and Mental Health: A Cross-Sectional Study in a Sample of University Students in the United States

Abstract: BackgroundThe sustained rise in negative mental health reports among university students is a source of continued global concern, and investigation continues into potential contributors to this rise. This includes the increased prevalence of risky sexual behaviors. Related is the increased prevalence of pornography use. Our study sought to explore the potential relationship between compulsive use of pornography and mental health in university students.MethodsOur sample consisted of university students (N = 103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 143 publications
(192 reference statements)
3
30
0
3
Order By: Relevance
“…Researchers believe that increased masturbation frequency is related to a decline in quality of life and sexual satisfaction (36), and frequent pornography use may also have a negative impact on sexual function and quality of life (37). A previous study reported that pornography was mainly used to relieve stress during the pandemic, to relieve loneliness and boredom (38), and to de-stress and release other pandemic-related negative emotions (39). Our study found that participants who postponed fertility treatment had more obvious symptoms of anxiety and depression than the control participants.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers believe that increased masturbation frequency is related to a decline in quality of life and sexual satisfaction (36), and frequent pornography use may also have a negative impact on sexual function and quality of life (37). A previous study reported that pornography was mainly used to relieve stress during the pandemic, to relieve loneliness and boredom (38), and to de-stress and release other pandemic-related negative emotions (39). Our study found that participants who postponed fertility treatment had more obvious symptoms of anxiety and depression than the control participants.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the impact of pornography on adolescents' cognitive, behavioral, and emotional responses has been widely investigated and reviewed [8,9]. Apprehension remains prominent about the negative impact of pornography on youth [8,[10][11][12][13][14]], yet research on the subject is inconclusive, and even positive effects of pornography have been reported [15,16]. Behavioral science research has shown that exposure to pornography can influence youth sexual attitudes, which, in turn, impact their sexual behavior [8,17] and socio-emotional functioning [12,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Apprehension remains prominent about the negative impact of pornography on youth [8,[10][11][12][13][14]], yet research on the subject is inconclusive, and even positive effects of pornography have been reported [15,16]. Behavioral science research has shown that exposure to pornography can influence youth sexual attitudes, which, in turn, impact their sexual behavior [8,17] and socio-emotional functioning [12,[18][19][20]. This may be especially relevant when exposure is frequent and may affect some adolescents more than others.…”
Section: Introductionmentioning
confidence: 99%
“… 14 In fact, POPU has been associated with higher relational problems 15 , 16 and lower mental health. 17 Notably, pornography, for its characteristics, may play a specific role in worsening users’ sleep quality 18 because it includes “any material designed to cause or enhance sexual arousal or sexual excitement in the viewer”, 19 and excessive pornography use is associated with increased stress and anxiety, 20 social impairment and isolation, 21 sexual dysfunctions 22 and sleep disturbances. 11 Indeed, Cacioppo et al 16 found that POPU was linked to psychological distress and emotional difficulties, which, in turn, were found to be associated with sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%